LA INCONSTITUCIONALIDAD DEL PROTOCOLO PARA LA EMISIÓN Y APLICACIÓN DE MEDIDAS ADMINISTRATIVAS DE PROTECCIÓN INTEGRAL DE DERECHOS A FAVOR DE LAS PERSONAS ADULTAS MAYORES POR VIOLENTAR EL PRINCIPIO CONSTITUCIONAL DE LEGALIDAD. - Díaz Alvarado, Geovanna Nathaly (2024)
The present research will systematize the requirements derived from the principle of legality and its execution in the administrative sanctioning procedure, with the objective of characterizing said principle as a limit to the punitive power of the State, in the determination of administrative responsibility and application of sanctions. The Decentralized Autonomous Municipal and Metropolitan Governments of the Ecuadorian State are part of the Public Administration and being characterized by their political, administrative and financial autonomy, they also have the power to impose penalties and have the competence to apply certain sanctions when an administrative infraction is committed, Therefore, it is necessary to establish that the principle of legality imposes limits to the Authorities and Institutions of the Public Administration, to protect the rights of the governed, a problem that is addressed in the study of the management of administrative sanctioning resolutions issued by the Cantonal Board for the Protection of Rights of the Autonomous Decentralized Municipal Government of Catamayo Canton. A qualitative methodology of interpretative scope is used, applying inductive and deductive methods, exegetical analysis and documentary analysis. The expected result is the adequate diligence of this principle in the administrative sanctioning procedure established in the Organic Administrative Code, for a better protection of the rights of the governed in the administrative sanctioning procedure established in Art. 25 of the PROTOCOL FOR THE ISSUANCE AND APPLICATION OF ADMINISTRATIVE MEASURES FOR THE INTEGRAL PROTECTION OF RIGHTS IN FAVOR OF THE ELDERLY IN THE CATAMAYO CANTON ISSUED BY THE AUTONOMOUS DECENTRALIZED GOVERNMENT OF CATAMAYO, which will have a positive impact on the guarantees of the rights of the persons subject to the sanctioning power of the Ecuadorian public administration the Ecuadorian public administration. In this work, the problem will be investigated from an administrative point of view, in order to establish whether the principle of legality is adequately applied in the administrative sanctioning procedure of the GADMC.